Validity of histopathological grading of articular cartilage from osteoarthritic knee joints. Issue 4 (1st April 1999) - Ostergaard, Keld; Andersen, Claus B; Petersen, Jorgen; Bendtzen, Klaus; Salter, Donald M
Abstract : OBJECTIVES: To determine the validity of the histological-histochemical grading system (HHGS) for osteoarthritic (OA) articular cartilage. METHODS: Human articular cartilage was obtained from macroscopically normal (n = 13) and OA (n = 21) knee joints. Sections of central and peripheral regions of normal samples were produced. Sections of regions containing severe, moderate, and mild OA changes were produced from each OA sample. A total of 89 sections were graded by means of the HHGS (0–14) twice by three observers. RESULTS: Average scores for regions designated severe (8.64) and moderate (5.83) OA were less than the expected (10–14 and 6–9, respectively) according to the HHGS, whereas average scores for the region designated mild (5.29) OA and central and peripheral regions (2.19) of normal cartilage were higher than expected (2–5 and 0–1, respectively). The HHGS was capable of differentiating between articular cartilage from macroscopically normal and OA joints and between the region designated severe OA and other regions. However, the HHGS did not adequately differentiate between regions designated mild and moderate OA. Values for sensitivity, specificity, and efficiency for all regions varied considerably. CONCLUSION: The HHGS is valid for normal and severe OA cartilage, but does not permit distinction between mild and moderate OA changes in articular cartilage.